Adeno-associated virus transformation into the normal miniature pig and the normal guinea pigs cochlea via scala tympani. (2nd September 2017) - Shi, Xunbei; Wu, Nan; Zhang, Yue; Guo, Weiwei; Lin, Chang; Yang, Shiming
Abstract: Objective: To investigate the expression of the miniature pig cochlea after AAV1 transfect into the cochlea via round window membrane (RWM). Methods: Twenty miniature pigs are equally divided into four experimental groups. Twelve miniature pigs are equally divided into four control groups. Each pig was transfected with the AAV1 in the experimental group via RWM and each pig was transduced with the artificial perilymph in the control group. The expression of green fluorescent protein (GFP) was observed at 2 weeks, 3 weeks and 4 weeks, respectively. Likewise, AAV1 was delivered into the guinea pigs cochleas using the same method, and the results were compared with that of the miniature pigs. Results: The expression was mainly in the inner hair cells of the miniature pig. The expression of GFP began to appear at 2 weeks, reached the peak at 3 weeks. It also expressed in Hensen's cells, inner pillar cells, outer pillar cells, spiral limbus, and spiral ligament. In the meanwhile, AAV1 was delivered into guinea pig cochlea via the same method, and AAV1 was also expressed in the inner hair cells. But the expression peaked at 2 weeks, and the efficiency of the inner hair cell transfection was higher than that of the pig. Conclusion: AAV1 can be transformed into miniature pig cochlea via scala tympani by the RWM method efficiently.